USING GIBBS’ REFLECTIVE CYCLE IN MAKING REFLECTIONS OF LITERARY ANALYSIS - Ikin Syamsudin Adeani; R. Bunga Febriani; Syafryadin Syafryadin (Indonesian EFL Journal, 2020)
In English as Foreign Language (EFL) classroom context, it is compulsory for the students to make reflections of literary works. The current study is aimed at examining how the students implement Gibbs’ reflective cycle in making reflections of literary analysis. The qualitative study employed a document analysis upon the students’ reflection artefacts. The students’ reflections are their responses to a short story written by Amy Tan. The findings of the study revealed that Gibbs’ reflective cycle is a good framework to be used by the students in writing reflections upon literary works they are working on. The well-structured framework of writing reflection helped the students explore the literary work deeply, since the reflective cycle accommodates important aspects that can be explored from the literary work by the students. It can be concluded from this study that among the models of reflective writing developed by Kolb, Johnson, and Gibbs, the latest model is considered the most suitable to be used in literary classroom since its well-structured model enables the students to write better reflections of literary works.Keywords: reflective writing; Gibbs’ reflective cycle framework; literary works; literary analysis.